UNMASKING TUBO-OVARIAN ABSCESS WITH ABSENCE OF CLASSIC SIGNS IN A 32-YEAR-OLD WOMAN AFTER A DECADE OF INFERTILITY - A CASE REPORT - Hansel Sanchia; Yoza Firdaoz; Alexander Alexander; RM Reza I Arnansyah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2025)
Tubo-Ovarian Abscess (TOA) is an infection in the adnexal area often caused by Pelvic Inflammatory Disease (PID). This infection is usually due to polymicrobial bacteria and can occur as a result of the spread of intra-abdominal infections. Symptoms include abdominal pain, fever, and leukocytosis, with additional symptoms such as vaginal discharge and nausea. Diagnosis is made through blood tests, imaging, and cultures. The primary treatment is antibiotics, and abscess drainage via surgery is considered if antibiotic therapy is ineffective. A 32-year-old woman with a history of an endometrial cyst presented with right lower quadrant pain and dysuria. Despite previously normal CA 19-9 and CA 125 levels, an ultrasound revealed an 8.33 cm cyst. The patient had a history of dysmenorrhea and no history of sexually transmitted infections. During surgery, a tubo-ovarian abscess with pus was discovered and subsequently drained. Post-operative recovery was successful, and the patient was discharged with a prescription for oral antibiotics and scheduled for outpatient follow-up. This case report highlights the absence of clinical manifestations such as fever or leukocytosis, which initially led to a misdiagnosis. This was only recognized after surgical intervention. The case illustrates that TOA can affect fertility, with the likely cause being a history of prior In Vitro Fertilization (IVF). These findings emphasize the importance of accurate diagnosis and a collaborative approach in managing TOA to improve patient outcomes. Further research is needed to understand the long-term impacts of TOA on reproductive health.